Crafting Polymeric and Peptidic Hydrogels for Improved Wound Healing. Issue 9 (5th March 2019) - Stern, David; Cui, Honggang
Abstract: Wound healing is a multifaceted biological process involving the replacement of damaged tissues and cellular structures, restoring the skin barrier's function, and maintaining internal homeostasis. Over the past two decades, numerous approaches are undertaken to improve the quality and healing rate of complex acute and chronic wounds, including synthetic and natural polymeric scaffolds, skin grafts, and supramolecular hydrogels. In this context, this review assesses the advantages and drawbacks of various types of supramolecular hydrogels including both polymeric and peptide‐based hydrogels for wound healing applications. The molecular design features of natural and synthetic polymers are examined, as well as therapeutic‐based and drug‐free peptide hydrogels, and the strategies for each system are analyzed to integrate key elements such as biocompatibility, bioactivity, stimuli‐responsiveness, site specificity, biodegradability, and clearance. Abstract : Supramolecular polymeric and peptidic hydrogels present effective alternatives for the treatment of complex acute and chronic wounds. Nonhealing wounds of this nature require constant medical intervention, placing a tremendous burden on patients. However, the tunability of hydrogels makes them conducive to wound healing by incorporating growth factors, cytokines, and therapeutic bioactive molecules in their design.